ANALISIS PEMBAGIAN WARISAN DAN WASIAT DALAM ISLAM BERDASARKAN AL-QUR’AN - Alya Nisma Fadhila Harahap; Ayu Aprila Bangun; Syah Fitri; Muhammad Rifai Harahap (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The system of inheritance in Islam is a legal framework based on the Qur'an and Hadith as the primary guidelines for the distribution of a deceased person's estate. This study employs a literature review method by examining various references related to Islamic inheritance law. The results indicate that the Islamic inheritance system has well-structured provisions, including the determination of eligible heirs, the distribution of their respective shares, the causes that entitle individuals to inherit, and the factors that may prevent them from receiving inheritance. In addition, a will (wasiyyah) serves as a complementary instrument in the distribution of wealth, with a maximum limit of one-third of the estate and without infringing upon the rights of the heirs. These provisions reflect the principles of justice, balance, and social responsibility within family and societal life. Therefore, the Islamic inheritance system is not only normative in nature but also plays an important role in maintaining harmony and preventing conflicts among heirs.